Legal Aspects of Identity Transactions Involving Entities with Foreign Elements: ICT Technologies and Issues of the Tax Burden - Samsin, I.; Kovalko, N.; Kovalenko, A.; Zabzaliuk, D.; Kurando, K. (Estudios de Economia Aplicada, 2021)
Legal analysis of transaction authentication with the participation of legal entities with a foreign element (LEFE) is interesting not only in disclosing theoretical and practical issues but also with difficulties and several features regarding foreign law application. The purpose of the article is to find the correct procedure for notarization of transactions on the territory of Ukraine with the participation of LEFE. In the research process, the authors combine theoretical developments and legislative instructions with practical experience of notarization. The research is based on four statements, which are confirmed during the study, contain a detailed description of the nuances to avoid possible errors and also offer to use a list of documents required to certification an undisputed transaction in Ukraine. The result of the article and its novelty is a detailed study of the actions of a notary in the certification of transactions involving LEFE, the presentation of a visual algorithm based on the above statements, namely: before the notary certificate it is necessary to determine whether the subjects of the transaction are LEFE; if a legal entity is established under the legislation of another state, then its civil and legal capacity is determined by the personal law of the state of such legal entity; there are certain restrictions on the activities of LEFE in Ukraine. The authors reviewed the recent changes in the taxation in Ukraine of LEFE, which must be taken into account; proposed the use of ICT technologies in notaries, what can not only simplify the process, help avoid subjective mistakes, but also open up new opportunities to streamline transactions involving entities with foreign elements.